If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7v + -9 = 10 + 6(v + 7) Reorder the terms: -9 + 7v = 10 + 6(v + 7) Reorder the terms: -9 + 7v = 10 + 6(7 + v) -9 + 7v = 10 + (7 * 6 + v * 6) -9 + 7v = 10 + (42 + 6v) Combine like terms: 10 + 42 = 52 -9 + 7v = 52 + 6v Solving -9 + 7v = 52 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. -9 + 7v + -6v = 52 + 6v + -6v Combine like terms: 7v + -6v = 1v -9 + 1v = 52 + 6v + -6v Combine like terms: 6v + -6v = 0 -9 + 1v = 52 + 0 -9 + 1v = 52 Add '9' to each side of the equation. -9 + 9 + 1v = 52 + 9 Combine like terms: -9 + 9 = 0 0 + 1v = 52 + 9 1v = 52 + 9 Combine like terms: 52 + 9 = 61 1v = 61 Divide each side by '1'. v = 61 Simplifying v = 61
| 3z=2.9+0.4 | | -15x-3y=5 | | 3-6=11+2x | | 10x-5+8x=5(6x-2)+2 | | 7y-21x=7 | | -4=w-3/4 | | 0.6m=-18 | | (x)(x+1)=10x | | 7+9=11(z-8) | | 2x^2+17x-55=0 | | -16t^2+96t+80=124 | | 2/7m-1/3=4/5 | | 20+20+z=-20+5z | | -2y+16=4x | | -16t^2+96t+80=125 | | 28=3(2p-6) | | 7h(11h-8)= | | 3x(2x+20)=180 | | Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) |